PAIN MANAGEMENT IN CRITICALLY ILL-INTUBATED PATIENT: A LITERATURE REVIEW - Ardia Putra (Fakultas Keperawatan-Universitas Syiah Kuala, 2011)
ABSTRACTBACKGROUND: Pain is classified as one of the least understood symptom because it is a subjective conceptand only can be defined by the individual who experiencing the pain. Among critical care patients, pain alsobeing a problem to be managed. This condition based on the reason that the patients in ICU were sufferingby complex problems and considered in a life threatening condition. PURPOSE: The purposes of this studyexplore the pain management among critically-ill intubated patient.METHOD: A relevant literature searched from databases: PubMed, CINAHL, the Cochrane and ProQuest Medical Library, and Science Direct were conducted. Key words used to retrieve included pain management, pain assessment tool, intubated and unconscious patient, and critically ill patient. Searching was limited in English language, full text, and the year of publication starting from 1994. RESULTS: Twenty-four related studies were intensivelyreviewed. Firstly, the concept of pain in critical care was described. Then, the barriers of pain assessmentand management, pain related factor in intensive care unit, and pain assessment tools in critically illintubated patientare explained. Moreover, in order to develop appropriate pain management in critically illintubated patient, the pharmacological and non-pharmacological intervention are reviewed. Finally, the nursing roles and activities for appropriate pain management in critically ill-intubated patients are described later.CONCLUSION: Literatures showed that critical care nurses (CCNS) holding the roles and responsibilities to deliver appropriate pain management in critically-ill intubated patients. This requirement are important in order to relieving and diminishing pain that feel among critical care patient, in particular unconscious and uncommunicative patients who cannot provide self report regarding their pain intensity andseverity.Keywords: Pain management, pain assessment, unconscious patient, critical care, and critically-illintubatedpatient.